Neobenedenia melleni Parasite of Red Snapper, Lutjanus erythropterus, with Regression Statistical Analysis between Fish Length, Temperature, and Parasitic Intensity in Infected Fish, Cultured at Jerejak Island, Penang, Malaysia. (6th April 2016) - Ravi, Rajiv; Yahaya, Zary Shariman
Abstract : The fish parasites collected from Lutjanus erythropterus fish species showed a correlation with parasitic intensity, fish size, and temperature, and statistical model summary was produced using SPSS version 20, statistical software. Statistical model summary concluded that among the variables which significantly predict the prevalence of Neobenedenia melleni parasites are fish length and water temperature, both significant at 1% and 5%. Furthermore, the increase in one unit of fish length, holding other variables constant, increases the prevalence of parasite by approximately 1 (0.7≈1) unit. Also, increasing the temperature from 32°C to 33°C will positively increase the number of parasites by approximately 0.32 units, holding other variables constant. The model can be summarized as estimated number of Neobenedenia melleni parasites = 8.2 + 0.7⁎ (fish length) + 0.32⁎ (water temperature). Next, this study has also shown the DNA sequence and parasitic morphology of Neobenedenia melleni . Nucleotide sequence for 18s ribosomal gene RNA in this study showed 99% similarity with N. melleni EU707804.1 from GenBank. Finally, all the sequence of Neobenedenia melleni in this study was deposited in GenBank with accession numbers of KU843501, KU843502, KU843503, and KU843504.